(Invited) Advanced Semiconductor Devices for Future CMOS Technologies. (27th March 2015) - Claeys, Cor; Chiappe, Danielle; Collaert, Nadine; Mitard, Jerome; Radu, Juliana; Rooyackers, Rita; Simoen, Eddy; Vandooren, Anne; Veloso, Anabela; Waldron, Niamh; Witters, Liesbeth; Thean, Aaron
Abstract : Device scaling for higher performance and lower power consumption requires the introduction of advanced process modules, new materials new device architectures and finally even the use of alternative device operation principles compared to the standard MOS transistor. Several of these advanced devices will be discussed in view of their scalability and their potential for coping with the ITRS roadmap. Key performance parameters will be investigated.